Aβ stimulates microglial activation through antizyme‐dependent downregulation of ornithine decarboxylase. Issue 6 (11th November 2018) - Cheng, Yu‐Wen; Chang, Chun‐Cheng; Chang, Ti‐Sheng; Li, Hsin‐Hua; Hung, Hui‐Chih; Liu, Guang‐Yaw; Lin, Chih‐Li
Abstract: Alzheimer's disease (AD) is one of the most prevalent neurodegenerative disorders. Its pathology is associated with the deposition of amyloid β (Aβ), an abnormal extracellular peptide. Moreover, its pathological progression is closely accompanied by neuroinflammation. Specifically, Aβ‐associated microglial overactivation may have the central role in AD pathogenesis. Interestingly, arginine metabolism may contribute to the equilibrium between M1 and M2 microglia. However, little is known about the involvement of arginine metabolism in Aβ‐induced microglial neuroinflammation and neurotoxicity. Moreover, the underlying mechanism by which Aβ induces the transition of microglia to the M1 phenotype remains unclear. In this study, we investigated the role of Aβ in mediating microglial activation and polarization both in vitro and in vivo. Our results demonstrated that under the Aβ treatment, ornithine decarboxylase (ODC), a rate‐limiting enzyme in the regulation of arginine catabolism, regulates microglial activation by altering the antizyme (AZ) + 1 ribosomal frameshift. Furthermore, the restoration of ODC protein expression levels has profound effects on inhibition of Aβ‐induced M1 markers and thus attenuates microglial‐mediated cytotoxicity. Altogether, our findings suggested that Aβ may contribute to M1‐like activation by disrupting the balance between ODC and AZ in microglia. Abstract : Our results revealed that ornithine decarboxylase (ODC) and polyamines may regulate M1 microglial activation via alterations in antizyme (AZ) + 1 ribosomal frameshifting during the amyloid β (Aβ) treatment. In addition, the restoration of ODC protein expression levels in BV2 microglia has profound effects on M1 phenotype inhibition and attenuates Aβ‐induced microglial‐mediated cytotoxicity.